Ventriculosubgaleal shunt placement for hydrocephalus in osteogenesis imperfecta with novel compound heterozygous CRTAP variants - Shintaro Nakamura; Kyosuke Ibi; Hiroyuki Tanaka; Hirokazu Takami; Keita Okada; Nao Takasugi; Motohiro Kato; Naoto Takahashi; Takanobu Inoue (Human Genome Variation)
Abstract Osteogenesis imperfecta is characterized by frequent fractures, bone deformities, and other systemic symptoms. Severe osteogenesis imperfecta may progress to hydrocephalus; however, treatment strategies for this complication remain unclear. Here, we describe severe osteogenesis imperfecta in an infant with symptomatic hydrocephalus treated with ventriculosubgaleal shunt placement. Targeted next-generation sequencing revealed novel compound heterozygous CRTAP variants, i.e., NM_006371.5, c.241 G > T, p.(Glu81*) and NM_006371.5, c.923-2_932del. We suggest that ventriculosubgaleal shunt placement is an effective and safe treatment for hydrocephalus in patients with severe osteogenesis imperfecta.